Two novel mutations in exon 3 of PHOX2B gene: think about congenital central hypoventilation syndrome in patients with Hirschsprung disease - Maria Giovanna Paglietti; Claudio Cherchi; Federica Porcaro; Emanuele Agolini; Alessandra Schiavino; Francesca Petreschi; Antonio Novelli; Renato Cutrera (BMC, 2019)
Abstract Background Congenital central hypoventilation syndrome (CCHS) is characterized by alveolar hypoventilation increasing during sleep and affected patients are unable to perceive and respond to hypercarbia with increased ventilation and arousal during sleep. PHOX2B gene mutations are considered as responsible for CCHS. Most of patients with CCHS are heterozygous for polyalanine expansion mutations (PARMs) in exon 3, but 10% of patients with classic CCHS are heterozygous for non-polyalanine expansion mutations (NPARMs) of the PHOX2B gene. Methods Data are collected on 3 patients affected by CCHS who referred to the Paediatric Pulmonology Unit of Bambino Gesù Children's Hospital (Rome, Italy) for a multidisciplinary follow-up program between 2000 and 2017. Results We describe three cases of patients affected by CCHS for which two novel mutations on exon 3 of PHOX2B gene were detected. Conclusions The description of these novel mutations and related clinical phenotypes allows to expand the knowledge into NPARM spectrum. Since the presence of Hirschsprung disease is related to NPARMs and the number of alanine repeats, we suggest performing CCHS genetic investigation and periodical assessment also in patients without a clear history of CCHS but affected by Hirschsprung disease. Trial registration Data are retrospectively collected.